Audit committee experts and earnings quality - Nelson, Sherliza Puat; Devi, Susela (Emerald Group Publishing Limited, 2013)
Purpose – The purpose of this paper is to investigate the relationship between audit committee expertise and financial reporting quality. Since the Sarbanes Oxley Act, 2002, there has been growing interest in the research concerning audit committee expertise, especially as the Security Exchange Commission requires firms to identify their audit committee financial experts. Design/methodology/approach – Based on two theories, the resource dependence theory and agency theory, the study examines the association of audit committee experts with financial reporting quality, proxied by earnings management. Samples involved 2008 financial data of 300 firms that were ranked by highest market capitalisation. In total, four types of expertise are developed based on academic qualification, professional qualification and work experience. Findings – Presence of non-accounting experts and accounting experts is significant to reduce the magnitude of earnings management. Other than that, leverage and firms size are also found to be significant. Originality/value – The findings show RDT is prevalent in accounting or auditing domain, where there is evidence showing directors bridge firms with external resources such as expertise and experience. Subsequently, contribute to the mainstream accounting literature that the resource dependence theory is also vital in explaining situations where directors’ expertise and knowledge are involved.